التوجه الجديد للدبلوماسية الاقتصادية الجزائرية نحو منطقة التجارة الحرة الإفريقية: الحوافز والرهانات - قرة فارس; لموشي طلال (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الدراسة إلى مسائلة مدى فعالية الأداء الاقتصادي للدبلوماسية الجزائرية في إطار توجهاتها نحو منطقة التجارة الحرة الإفريقية. وللإجابة عن هذه الإشكالية تم الإستعانة بالمدخل النيو-ليبيرالي ومدخل الاقتصاد السياسي. وقد توصلت هذه الدراسة إلى أن فعالية الدبلوماسية الاقتصادية الجزائرية في ظل توجهها نحو هذه المنطقة الحرة، ترتبط بقدرتها على لعب دور الفاعل المؤثر من خلال التأسيس لإقتصاد قوي قائم على التنوع والإنتاجية والقدرة على المنافسة في السوق الإفريقية، والعمل على احتواء التحديات المواجهة وفق مقاربة براغماتية تهدف للحفاظ على المصلحة الوطنية. Abstract: This study aims to examine the effectiveness of the economic performance of Algerian diplomacy in its orientation towards the African Continental Free Trade Area (AfCFTA). To answer this problem, both the neoliberal and political economy approaches have been used. The study found that the effectiveness of Algeria’s economic diplomacy towards the African Free Trade Area is related to its ability to play the role of an "influential actor", by establishing a strong economy based on diversity, productivity and competitiveness in the African market, and by working to contain various challenges in a pragmatic manner to preserve the national interest.